A GAME THEORETIC ANALYSIS OF VOLUNTARY EUTHANASIA AND PHYSICIAN ASSISTED SUICIDE. (4th November 2019) - Harrison, Rodrigo; Silva, Francisco
Abstract : In countries/states where voluntary euthanasia (VE) or physician‐assisted suicide (PAS) is legal, the patient's decision about whether to request VE or PAS heavily relies on the information others provide. We use the tools of microeconomic theory to study how communication between the patient, his family and his physician influences the patient's decision. We argue that families have considerable power over the patient and that the amount of information that is transmitted from physician to patient might be severely diminished as a result of legalizing VE or PAS. We discuss our main results in the context of the ongoing normative debate over the legalization of VE and PAS. (JEL D8, I12)